1992
DOI: 10.1002/pd.1970120607
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of a false‐negative finding in both direct and culture of a chorionic villus sample

Abstract: A discrepancy is reported between the karyotype of both direct and cultured chorionic villus cells (46,XX) and a fetal skin biopsy (47,XX, +18). The significance of this result is discussed and compared with similar discordant findings reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Of the 91 mosaic findings, no less than 17 showed complete discordance between the karyotypes of direct preparations and cultured cells ( Table 4 also includes the only entirely false-negative result, a trisomy 18 fetus with a normal result from both direct preparations and cultured cells, reported to the U.K. study (Pindar et al, 1992).…”
Section: Resultsmentioning
confidence: 95%
“…Of the 91 mosaic findings, no less than 17 showed complete discordance between the karyotypes of direct preparations and cultured cells ( Table 4 also includes the only entirely false-negative result, a trisomy 18 fetus with a normal result from both direct preparations and cultured cells, reported to the U.K. study (Pindar et al, 1992).…”
Section: Resultsmentioning
confidence: 95%
“…In contrast to the extensive literature data on chromosomal mosaicism in STC and LTC and its implication for false-positive findings, there are only few data on false-negative findings, mainly reported as single cases (Eichenbaum et al, 1986; Linton and Lilford, 1986;Martin et al, 1986;Simoni et al, 1987;Smidt-Jensen and Lind, 1987;Callen et al, 1988;Eiben et al, 1988;Leschot et al, 1988;Wirtz et al, 1988;Bartels et al, 1989;Hammer et al, 1991;Pindar et al, 1992). The false-negative fndings are almost always restricted to STC and for a long time no false-negative findings were known.…”
Section: Resultsmentioning
confidence: 99%
“…In three cases, the (semi)direct method was normal, the culture was non-mosaic abnormal, and chromosome studies of the blood (1997) of the child showed a mosaic sex-chromosomal abnormality. In the case reported by Pindar et al (1992), the (semi)direct as well as the culture method gave a false-negative result (46,XX), whereas the child had a 47,XX,+18 chromosomal pattern. By this new case it is again demonstrated that the most favourable technique for accurate prediction is the combination of the (semi)direct and culture method.…”
mentioning
confidence: 88%
“…v a post-zygotic non-disjunction in the inner cell mass during embryogenesis (Crane and Cheung, 1988); v a twin pregnancy, with loss and re-absorption of the normal fetus; v a mosaic situation, undetected because of the low mitotic index; and v contamination of the villi with normal maternal cells (Pindar et al, 1992).…”
mentioning
confidence: 99%